(The ultimate sticker book) Dog - Alderman, Pat (Dk Publishing UK, 1993)
The Ultimate Dog Sticker Book is an engaging and interactive resource for dog lovers, featuring over 60 reusable stickers of various dog breeds. The book provides fun facts about each breed, including their characteristics, behaviors, and care needs. Through colorful illustrations and playful activities, readers can learn about different dog types while creating their own dog-themed scenes. This sticker book combines education and creativity, making it an enjoyable way for children and dog enthusiasts to explore the world of dogs.